Deteksi ekspresi gen fusi Bcr-Abl pada All dewasa: seb.uah laporan kasus = Expression Detection of bcr-abl Fusion Gene in Adult ALL :A Case Report - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Leukemia is hematologic malignancy caused by excess proliferation of hematopoetic or lymphoid cells that affect everybody, ages and sex. Leukemia races in Indonesia is a lot enough (Â± 7000 cases/year) with mortality rate 83,6%. Diagnosis is based on FAB classification morphology. The fact, WHO classification 2000 has been used worldwide based on cytogenetic and molecular biology profile can define the clonal diseases more precisely and choose the adequate therapy. In adult, ALL case is rare, only 15-30% of all adult leukemia cases and most of the cases is related with t(9